Side effects of drugs used in cancer chemotherapy - Oktawia Julia Pylak-Piwko; Barbara Nieradko-Iwanicka (Journal of Education, Health and Sport, 2017)
Introduction Chemotherapy is a systemic treatment of tumors with use of cytotoxic agents which affect the whole organism destroying cells tumor cells which divide quickly. These medicines damage also healthy tissues of the organism causing some side effects in different systems of organs.